Perawatan dan Perbaikan Sistem Hidrolik pada Dumping Dump Truck Mitsubishi Fuso 190Ps - Fajri Alrazzak; Jeri Mahyuda; Menhendry; Zulfikar (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2021)
The hydraulic system in a dump truck that consists of several components requires a planned maintenance action, so that the hydraulic system can function optimally. The purpose of writing is to be able to do damage analysis and can take corrective actions appropriately and correctly. The analytical method in the analysis of maintenance and repair of hydraulic systems is to use several questions, namely what, why, where and how. The main components of dump truck hydraulic systems that require maintenance are hydraulic tanks, pumps, valves, actuators, filtration and hydraulic hose, while the main causes of damage from hydraulic system components are due to poor hydraulic oil cleanliness, contamination in the system, and overload ( over load). To overcome the damage that occurs is by implementing management care and repair that is correct, planned and in accordance with the SOP.